"Must-Work": A Scalable Model for Parallel Recursive Problems on P2P Networks - Amad, M.; Aissani, D.; Bellal, T.; Amrioui, H. (Informatica)
"Must-Work": A Scalable Model for Parallel Recursive Problems on P2P Networks